Analysis of Social and Cultural Values in the Tedhak Siten Tradition: An Ethnopedagogical Study - Syaiful Bahri; I Wayan Suastra; Ida Bagus Putu Arnyana (Universitas Muhammadiyah Enrekang, 2024)
The objective of this research is to conduct an ethnopedagogical study of the social and cultural values embedded in the Tedhak Siten tradition. The research employs a qualitative descriptive method, utilizing interviews and field observations for data collection. The findings reveal that the Tedhak Siten tradition is preserved by the people of Sumenep, particularly in Parsanga Village, with a relatively simple presentation. The Tedhak Siten tradition embodies both social and cultural values, which are reflected in its rituals, including the recitation of shalawat, stepping on seven colored steps, climbing a ladder, entering a chicken coop, and sweeping with a broomstick. Keywords: Tedhak Siten, Social Values, Cultural Values.